Post-Breast Surgery Pain Syndrome: Shifting a Surgical Paradigm. Issue 7 (22nd July 2021) - Beederman, Maureen; Bank, Jonathan
Abstract : Summary: Post-mastectomy pain syndrome and the less well-described post-breast surgery pain syndrome are long-term neuropathic pain conditions that may affect more than 50% of patients after mastectomy and breast surgery. While the etiology, risk factors, and management have been reviewed in our literature, we offer here a focused outline that will gear the plastic surgeon with tools to lead a multidisciplinary, algorithmic approach to the care of patients with post-mastectomy pain syndrome/post-breast surgery pain syndrome. After reading this article, we hope the reader will have improved awareness of post-mastectomy pain syndrome/post-breast surgery pain syndrome, and thus be able to incorporate appropriate treatments and preventative steps into their primary surgical routine.